The β-Lactamase Inhibitor Boronic Acid Derivative SM23 as a New Anti-Pseudomonas aeruginosa Biofilm - Peppoloni, Samuele; Pericolini, Eva; Colombari, Bruna; Pinetti, Diego; Cermelli, Claudio; Fini, Francesco; Prati, Fabio; Caselli, Emilia; Blasi, Elisabetta (Frontiers in microbiology, 2020)
is a Gram-negative nosocomial pathogen, often causative agent of severe device-related infections, given its great capacity to form biofilm. finely regulates the expression of numerous virulence factors, including biofilm production, by Quorum Sensing (QS), a cell-to-cell communication mechanism used by many bacteria. Selective inhibition of QS-controlled pathogenicity without affecting bacterial growth may represent a novel promising strategy to overcome the well-known and widespread drug resistance of . In this study, we investigated the effects of SM23, a boronic acid derivate specifically designed as β-lactamase inhibitor, on biofilm formation and virulence factors production by . Our results indicated that SM23: (1) inhibited biofilm development and production of several virulence factors, such as pyoverdine, elastase, and pyocyanin, without affecting bacterial growth; (2) decreased the levels of 3-oxo-C -HSL and C -HSL, two QS-related autoinducer molecules, in line with a dampened / system; (3) failed to bind to bacterial cells that had been preincubated with conditioned medium; and (4) reduced both biofilm formation and pyoverdine production by onto endotracheal tubes, as assessed by a new model closely mimicking clinical settings. Taken together, our results indicate that, besides inhibiting β-lactamase, SM23 can also act as powerful inhibitor of biofilm, suggesting that it may have a potential application in the prevention and treatment of biofilm-associated infections.